If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 42 + -5y Solving y = 42 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. y + 5y = 42 + -5y + 5y Combine like terms: y + 5y = 6y 6y = 42 + -5y + 5y Combine like terms: -5y + 5y = 0 6y = 42 + 0 6y = 42 Divide each side by '6'. y = 7 Simplifying y = 7
| -1.14*23.25+47= | | y=0.63(0.5)x | | 3/8x-8=-7 | | -.71*23.25+37= | | 8x^3=(-64) | | =(n-5)(2n+4) | | 3(x-2)+(x-12)/6-2*(x+3)/(6)=x/2 | | 20+4k=228 | | 3x=4+x+16 | | 72-5x=8x+16 | | 8x-6=4x+14 | | r/7=-9/7 | | (3x+5)(2x-3)=-5 | | 6x+8=4x-2 | | m/15=-11/15 | | 12=-3(-6x-3) | | x^4+x^3+x^2+3x-6=0 | | z^4+z^3+z^2+3z-6=0 | | -1/3x=4 | | -.71x+37=-1.14x+47 | | p/12=-1/3 | | 63x=36(x+40) | | -5x-(18)=-45-2x | | 24x^2-16x-89=0 | | x+3=-11 | | -5x-18=-45-2x | | -5x-18=2x-(-45) | | 30x=20(x+15) | | v/9=-14 | | 24(x+30)=40x | | 40x=24(x+30) | | 2a(5a+3b)= |